ANALISIS PERSEPSI KONSUMEN TERHADAP KONSEP PRODUK MICROCAR ARINA - susbiyantoro susbiyantoro (JURNAL LENTERA BISNIS, 2017)
ABSTRACT The National otomotive industry in Indonesia has a very good prospect. Domestic market is very potential for developing transportation device, because it supported by the wide landscape o Indonesian region and the large amount of Indonesian population. However, the presence of national car industry not directly implicate to the probability of product absorption massively. Government support in matter of economy policy, bureaucracy  and national car development technique are not the main factor that giving the possibilities for product selling success. The success for national car selling still determined by how big the market can accept the product concept.Arina Motor Manufacturing is the company that recently developing the Microcar national car prototype with the brand ARINA. Recently, target market for this product is domestic/local market. The first indication for helding this research is the necessity of the new product testing for getting market response. The problems that indicated as the cause are the product concept it self such as quality, feature, style and design, also the perception from the future consumer to Arina Microcar. This research has an intend to examine much further of the marketing mix analysis, especially that related with the product concept of ARINA Microcar as one of the national car excellence product prototype.The research was held on Jakarta Indonesian International Motor Show (IIMS) at July 24th – August 02nd, 2009. The survey was held by spreading the questioner to respondents for the intend to get some information that related with some factors in marketing mix from the product concept view that influence consumer perception toeward ARINA Microcar. The data processing for the this research is processed by using SPSS Program.The result of this research shows that all research variable are valid and reliable. Based on factor analysis testing, all variable fulfill the properness condition and connected each other, because the gained data KMO > 0.50. Meanwhile, the analysis result correlation shows that the future consumer perception toward ARINA Microcar product concept is not significantly determined by quality variable (29.9%), but determined by feature variable (52.7%), and style/design (64.4%). In the meantime, regression analysis result also shows valid with some indicators such as data already normal distributed, there is no autocorelation, and there is no colinearity. The F test results shows that all variable by collectively influence to the perception. But the result  of the T test shows only feature variable and style/design that separately influence to the perception.   Keywords: Product Quality, Features, Style and Design, Consumer Perception